Single-Nucleotide Polymorphisms in IL23R-IL12RB2 (rs1495965) Are Highly Prevalent in Patients with Behcet's Uveitis and Vary Between Populations. (4th July 2019) - Kramer, Michal; Hasanreisoglu, Murat; Weiss, Shirel; Kumova, Deniz; Schaap-Fogler, Michal; Guntekin-Ergun, Sezen; Ozdek, Sengul; Gurelik, Gokhan; Ergün, Mehmet Ali; Goldenberg-Cohen, Nitza; Cohen, Yoram
ABSTRACT: Purpose : To test the frequency of single-nucleotide polymorphisms in the IL-10, IL23R-IL12RB2 genes in patients with Behcet's uveitis. Methods : Blood samples were collected from 89 Israeli and Turkish patients, and from healthy control subjects of different origins. Genomic DNA was extracted from peripheral blood leukocytes and genotyped. Results : The risk allele, A, in rs1800871, of IL-10 gene was highly prevalent in Behcet's uveitis and healthy control samples alike; highest among the Turkish groups. Prevalence of G allele, in rs1495965, in the IL23R-IL12RB2 gene was high in Behcet's uveitis patients, and among healthy Turkish and Israelis of Middle Eastern origin, while lower among the other Israeli control group (77.9%, 78.9%, 27.8%, respectively, P  < 0.001). Conclusion : Our findings highlight the differences between populations and may account for the increased prevalence of the disease among Turkish and Israelis of Middle Eastern origin. Further studies are required to map other healthy and affected populations.